Validation of the Spanish Version of the Lucidity and Consciousness in Dreams Scale - García-Campayo, Javier; Moyano, Nieves; Modrego-Alarcón, Marta; Herrera-Mercadal, Paola; Puebla-Guedea, Marta; Campos, Daniel; Gascón, Santiago (Frontiers in Psychology, 2021)
Lucid dreaming, a specific phenomenon of dream consciousness, refers to the experience being aware that one is dreaming. The primary aim of this research was to validate a Spanish version of the Lucidity and Consciousness in Dreams scale (LuCiD). A secondary aim was to explore whether meditation experience and mindfulness trait were related to LuCiD scores. Data from 367 Spanish men (34.6%) and women (65.4%) who completed LuCID, the Five Facets of Mindfulness Questionnaire (FFMQ) and the Positive and Negative Affect Schedule (PANAS) were examined. From the total sample, 40.3% indicated some experience with formal meditation (meditators), while 59.7% did not have any meditation experience (nonmeditators). A random subsample of 101 participants, who completed LuCiD for a second time after a period of 10–15 days, was used for test-retest reliability analysis. The LuCiD scale comprises 28 items distributed across 8 factors: insight, control, thought, realism, memory, dissociation, negative emotion and positive emotion. Factor structure, reliability by both internal consistency and test-retest reliability, and construct and concurrent validity were tested. Confirmatory factor analysis (CFA) confirmed the original 8-factor model, showing goodness of fit in contrast to a single-factor model. Item 15 was deleted from the Dissociation factor as it performed poorly (i.e., skewness and kurtosis, non-normal distribution of responses, and corrected item-total correlation under .40). The scale showed adequate values of internal consistency (between  = 0.65 for Memory and  = 0.83 for Positive Emotion) and test-retest reliability by significant Pearson correlations (p <.001) for each factor. The scores of meditators were higher for the LuCiD scale Insight and Dissociation factors, in contrast with those of nonmeditators. The Observing facet of mindfulness was positively associated with all LuCiD factors, except Realism and Positive Emotion, and the Acting with Awareness facet showed a negative correlation with the LuCiD factor Realism. Finally, positive and negative affect were associated with the LuCiD factors Positive Emotion and Negative Emotion. This study provides a valid and reliable measure for exploring lucidity and consciousness in dreams for a Spanish population, Moreover, the results suggest a relationship with meditation experience, mindfulness trait and positive and negative affect.